Investigation into accurate location and orientation of IMU for sensor scanning application - Prakash, Mudita (Nanyang Technological University, 2020)
The problem of imaging is now been lingering for long. Various methods have been tested and framed for imaging of cracks on metallic and non-metallic surfaces. The methods which are commonly in use are of Machine Vision, Microwave or radar imaging. A new method of imaging using mm-Wave radar has been introduced which uses a frequency range of 76-81 GHz. It is better than previous methods because of higher bandwidth which supports higher data rate thereby giving a better image output. The drawback with mm-Wave imaging is that the sensors present in the market are not well tuned to work with high frequency systems. Therefore, in this work mm-Wave technique has been further fine- tuned using IMU sensors which eliminated the disadvantage of sensor bias and measurement errors. The project work basically focuses on the determination of accurate location and orientation of IMU which can be further used for various sensor scanning applications. It utilizes MPU 9250 interfaced with Arduino Uno to determine the orientation and position of the crack. The position and orientation are determined by taking the combination of the measurements of the readings from the accelerometer, magnetometer and gyroscope of the Inertial Measurement Unit (i.e. MPU9250) with the help of Extended Kalman Filter. The velocity and displacement were derived from the MPU9250 data using trapezoidal integration method. The displacement was combined with the acceleration of the MPU9250 to determine the velocity of it. With the use of high precision sensors and a high-performance micro-controller the efficiency can be further increased.